ANALISIS PENGALOKASIAN DANA DESA TERHADAP PEMBANGUNAN INFRASTRUKTUR DESA DI KECAMATAN KOTO GASIB KABUPATEN SIAK - Cici Annike Wulan; Syafril Basri; Sri Endang Kornita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to determine the allocation of village funds to the development of village infrastructure in Koto Gasib subdistrict Siak regency in this study the population of research is all village and community apparatus located in Koto Gasib District consists of 12 villages, sampling in this research using key-informant assistance so as to obtain key-informant as much as 77 respondents, consist of 22 respondents from apparatus villages and 55 respondents from the community. The method of analysis in this study is in the form of explanatory research. Measurements made in this study is to use questionnaires in the form of determining the scale of research, using the existing Likert Data Scale is processed and analyzed by using tabulation data, while the technique of analyzing is to use quantitative and qualitative data analysis Based on the results of the research, it is known that the total budget of village development in Koto Gasib subdistrict of Siak regency is Rp 8,948,271,786, - with financial realization equal to Rp 6,499,672,922, - where 72,90% activity of financial realization of village development from village fund (DD) when viewed from the realization of village funds that have been implemented in the district of Koto Gasib has been allocated well that is equal to 72.90%. The allocations have been in accordance with government provisions where the purpose of allocating village funds (DD) one of them improves village infrastructure.Keywords: Allocation, Village Infrastructure, Village Fund (DD)